Calculus

posted by .

Convert to a rectangular equation by eliminating the parameter:
x=sin(theta)
y=(cos theta)^2

  • Calculus -

    from y = cos^2 Ø
    y = 1 - sin^2 Ø
    sin^2 Ø = 1-y
    sinØ = √(1-y)

    so sinØ = x and sinØ = √(1-y) , so

    x = √(1-Y)
    or
    x^2 = 1-y

Respond to this Question

First Name
School Subject
Your Answer

Similar Questions

  1. calculus

    conic sections prove that the line x-2y+10=0 touches the ellipse 9x^2+64y^2=576 show that the equation of the normal to the ellipse x^2/a^2 + y^2/b^2 = 1 at the point (a cos theta, b sin theta ) is ax sin theta - by cos theta - (a^2-b^2) …
  2. Calculus

    I wanted to confirm that I solved these problems correctly (we had to convert the polar curves to Cartesian equations). 1.rcos(theta)=1 x=1 2.r=2*sin(theta)+2*cos(theta) r^2=2rsin(theta)+2rcos(theta) x^2+y^2=2y+2x (a little unsure …
  3. Pre-Calculus

    translate this polar equation into a rectangular form: rsin(2theta)=sin(theta) My answer: r2sin(theta)cos(theta)=sin(theta) 2rcos(theta)=1 2x=1 x=1/2 This is the only answer I can get and someone told me it's wrong. Would someone please …
  4. trigonometry

    can you correct the rest for me please? Express each as a function of theta: a. sin (270deg + theta)= cos theta b. cos (pi + theta)= -cos theta c. tan (810 + theta)= ?
  5. trigonometry

    can you correct the rest for me please? Express each as a function of theta: a. sin (270deg + theta)= cos theta b. cos (pi + theta)= -cos theta c. tan (810 + theta)= ?
  6. Algebra II

    Multiple Choice Which expression is NOT equivalent to 1?
  7. Precalculus 2

    Similiarly to a question I asked previously I took the same approach. the problem is: what value(s) of theta solve the following equation?
  8. Trigg

    How do I find a rectangular-coordinate equation for the curve by elimination the parameter?
  9. Trigonometry

    Prove the following identities: 1. (tan theta - sin theta)^2 + (1-cos theta)^2 = (1-sec theta) ^2 2. (1-2cos^2 theta) / sin theta cos theta = tan theta - cot theta 3. (sin theta + cos theta ) ^2 + (sin theta - cos theta ) ^2 = 2 Thank …
  10. Trigonometry

    Prove the following identities: 1. (tan theta - sin theta)^2 + (1-cos theta)^2 = (1-sec theta) ^2 2. (1-2cos^2 theta) / sin theta cos theta = tan theta - cot theta 3. (sin theta + cos theta ) ^2 + (sin theta - cos theta ) ^2 = 2 Thank …

More Similar Questions